Assessment of the reliability of technical electricity metering at an enterprise - Antypov, I.; Kryvonosov, V.; Petrenko, A.; Ivanchenko, A.; Bosenko, O. (Energy and Automation, 2025)
Technical metering of energy consumption enables enterprises to reduce electricity costs and manage power flows between workshop technological objects in a timely manner, contributing to increased profitability. The implementation of automated technical metering facilitates comprehensive monitoring of energy consumption modes, which includes analyzing not only the overall performance of the enterprise but also the operation of individual technological units and equipment during specific time periods. This approach allows the generation of detailed analytics regarding the efficiency of energy resource utilization. Creating such comprehensive analytics enables enterprises to evaluate energy efficiency and reduce consumption costs, determine the precise cost of production depending on production line load, optimize production processes considering energy expenditures, monitor reactive power consumption, and ensure its effective compensation.Automated metering allows enterprises to not only collect actual data on energy resource consumption but also forecast future consumption. This is particularly important for planning production processes, minimizing energy losses, and improving overall energy efficiency. Moreover, automated metering systems enable the timely detection and elimination of deviations in energy consumption, reducing the likelihood of exceeding permissible energy resource usage limits.The article presents a case study that demonstrates the efficiency and reliability of technical metering at a typical enterprise. The study also includes an analysis of the causes of measurement errors and provides practical recommendations for their minimization.Therefore, the implementation of modern automated technical metering systems is an essential step toward improving energy efficiency, reducing costs, and optimizing the management of power flows between workshop technological objects. This, in turn, enhances equipment productivity, improves control over energy resource utilization, and ultimately increases enterprise profitability.Key words: technical metering of energy resources, reactive power, measurement error, current transformer